PENGARUH SIRUP JAHE MERAH TERHADAP PENURUNAN HIPEREMESIS GRAVIDARUM GRADE I PADA IBU HAMIL DI PLUPUH SRAGEN - Suparmi Suparmi; Rita Riyanti Kusumadewi (Universitas Harapan Bangsa Purwokerto, 2018)
Nausea and vomiting can interfere and make fluid imbalances in kidney tissue and liver become necrosis. Based on the results of research in Indonesia obtained data of mothers with hyperemesis gravidarum reached 14.8% of all pregnancies. Complaints of nausea and vomiting occur in 60-80% primigravida and 40-60% multigravida. One in a thousand pregnancies these symptoms become more severe. Ginger contains essential oil that is refreshing and blocks vomiting reflexes while gingerol can promote blood circulation and nerves - the nerves work well. Objective: To determine the effect of consumption of red ginger syrup (Zingiber officinale Roscoe) on the reduction in grade 1 hyperemesis of gravidarum in Trimester I pregnant women in the work area of ​​Plupuh 1 Public Health Center in Sragen. Methods: A quasi-experimental study with non-equivalent pretest-posttest with control group, sampling quota sampling. The number of samples was 60 subjects (30 controls and 30 interventions). The treatment group was given red ginger syrup 2x a day (3-4 tablespoons of syrup diluted with 200ml warm water) for 10 days. the control group was not given red ginger syrup. Nausea and vomiting are measured by an observation sheet. Test statistics with T Test. Ethical eligibility permit No.1127/B.1/ KEPK-FKUMS/III/ 2018. Research Results: There was a significant difference in the frequency of nausea and vomiting after 10 days of experimentation between the two groups (p <0.001) where the frequency of nausea vomited the treatment group sample in day 10 was smaller than the frequency of nausea and vomiting of the control group sample. Conclusion: Giving red ginger syrup for 10 days in pregnant women can reduce grade 1 hyperemesis of gravidarum in pregnant women. (p value <0.001)